ApoD mediates age-associated increase in vulnerability to influenza virus infection - Zhimin Jiang; Wenliang Pan; Yu Chen; Dongliang Zhou; Shuning Ren; Qi Tong; Litao Liu; Honglei Sun; Yipeng Sun; Yuhai Bi; Dayan Wang; Lu Lu; et al. (Proceedings of the National Academy of Sciences, 2025)
Influenza A virus (IAV) infection causes significantly greater morbidity and mortality in the elderly population, but the molecular mechanisms in the aging process responsible for severe infection remain unclear. In this study, we found that increased severity in IAV infection and reduced innate immune response correlated with extensive mitophagy in senescent human cells and in the lung of aged mice. Apolipoprotein D (ApoD) was identified as strongly elevated in the lungs and sera of aged human (>65 y old) and mouse (>21 mo old). ApoD was able to localize to mitochondria and interact, through its WXXI motif in the LC3B-Interacting Region domain, with LC3B to trigger mitophagy during IAV infection, in a PINK1 pathway independent manner, which attenuated type I interferon response and promoted virus replication. ApoD deficiency, on the other hand, protected older mice from severe influenza and improved survival. Likewise, depletion of senescent cells by ABT-263, a senolytic compound, in aged mice lowered ApoD level and restored innate immune antiviral response, limiting virus propagation and associated pulmonary damage. Thus, age-induced ApoD drives IAV-mediated mitophagy, and promotes virus replication and infection severity, and is therefore a promising target for inhibition to improve disease outcome in older patients.